Implantación de la contabilidad comercial en la empresa “Alarmsemaxs Cia. Ltda.” En la ciudad de Loja, periodo febrero a marzo del 2013 - Sotomayor Guamán, Mayra del Rocío (2014)
This research work provides support to the society and Implement Commercial Accounting in Business "ALARMSEMAXS CIA. LTDA." adequate control of their operations and stocks will be achieved by providing a better service to its customers and the community at large, contributing to the economic development of society and therefore the country. We complied fully with the objectives, to implement an accounting system in the company "ALARMSEMAX" CIA. LTDA., applying the Perpetual Inventory System for the Merchandise Account Control, the transcript cards was developed using the weighted average method of valuation. Entire accounting process is performed from source documents to the preparation of financial statements; Likewise the statements for the months of February and March 2013 in relation to the declaration of Value Added Tax (IVA) in the form 104 and tax withholding tax obligations held in the form 103; finally the financial indicators were applied to determine the liquidity and solvency of the company. He completed the research work came to the conclusion that the company does not keep records of purchase and sale, or control of the goods; so the owners to implement an appropriate accounting system that allows you to get real and timely financial statements for correct decision making is recommended.